Willingness to participate in solid waste management amongst residents of Sembulan Tengah water village in Sabah, Malaysia - Marcilla Elmy Girl Girl Malasius; James Alin; Brian Dollery (AESS Publications, 2020)
Solid waste management presents significant challenges in many developing countries in Asia. In this paper we empirically investigate the willingness to participate (WTP) in solid waste management by residents of the Sembulan Tengah Water Village in Sabah, Malaysia by means of a survey study. Sembulan Tengah Water Village is a squatter community populated by poor people subsisting largely in the informal sector. The paper seeks to contribute to the existing empirical literature on the factors that significantly influence WTP generally, as well as WTP in terms of labour hours and pecuniary contributions. Using the binary logistic regression method, our results show that age, gender, educational level, length of stay, house ownership, and ethnicity significantly influence willingness to participate in solid waste cleaning activities. Age significantly influences WTP in terms of labour hours. Other factors, such as gender, education level, length of stay, income level, and house ownership, were significant in influencing WTP in terms of money. Our findings can be used for policy purposes to improve solid waste management in poor communities across developing countries in Asia and elsewhere.